2021
DOI: 10.1016/j.bpj.2020.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Sample Preparation and Imaging Conditions Affect mEos3.2 Photophysics in Fission Yeast Cells

Abstract: Photoconvertible fluorescent proteins (PCFPs) are widely used in super-resolution microscopy and studies of cellular dynamics. However, our understanding of their photophysics is still limited, hampering their quantitative application. For example, we do not know the optimal sample preparation methods or imaging conditions to count protein molecules fused to PCFPs by single-molecule localization microscopy in live and fixed cells. We also do not know how the behavior of PCFPs in live cells compares with fixed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…[ 38 ] This discrepancy may possibly be explained by the presence of strong additional illumination at 561 nm in optical microscopy experiments, resulting in enhanced photoconversion efficiencies. [ 39 ] We thus cannot exclude that photoconversion of mEos4b is based on a more complex scenario than the simple model proposed in Figure 8B , involving additional photo‐induced transformations and states. Future NMR experiments in the presence of both illumination lasers will allow to address this issue.…”
Section: Resultsmentioning
confidence: 98%
“…[ 38 ] This discrepancy may possibly be explained by the presence of strong additional illumination at 561 nm in optical microscopy experiments, resulting in enhanced photoconversion efficiencies. [ 39 ] We thus cannot exclude that photoconversion of mEos4b is based on a more complex scenario than the simple model proposed in Figure 8B , involving additional photo‐induced transformations and states. Future NMR experiments in the presence of both illumination lasers will allow to address this issue.…”
Section: Resultsmentioning
confidence: 98%
“…To test this, we monitored the progression of ensemble mEos4b red fluorescence under 1, 10, and 100 W/ cm 2 405 nm illumination and weak exposure to 561 nm light (8 W/cm 2 ) (Figure 3A). Sun et al 7 reported that the ensemble red fluorescence intensity of mEos3.2 under constant 405 and 561 nm illumination follows a three-state model: green → red → bleached. Such a model implies that the level of the maximum recorded red fluorescence increases with the applied 405 nm light intensity as bleaching by the 561 nm laser lowers the peak height at low 405 nm intensities.…”
mentioning
confidence: 75%
“…However, a disadvantage of mEos-based PCFPs is their highly complex photophysical behavior (Figure S1). …”
mentioning
confidence: 99%
“…3 However, a disadvantage of mEos-based PCFPs is their highly complex photophysical behavior (Supplementary Figure S1). [4][5][6][7] One property essential to the success of PALM experiments using PCFPs is the so-called photoconversion efficiency (PCE), 8,9 sometimes also referred to as signaling efficiency. 10 Typically, upon prolonged violet light illumination, green-to-red photoconversion remains incomplete, meaning that from a pool of PCFPs, only a limited fraction can ever be imaged in the red channel of the microscope.…”
Section: Toc Graphicsmentioning
confidence: 99%